Family Nurture Intervention in the Neonatal Intensive Care Unit improves social‐relatedness, attention, and neurodevelopment of preterm infants at 18 months in a randomized controlled trial. (11th March 2015) - Welch, Martha G.; Firestein, Morgan R.; Austin, Judy; Hane, Amie A.; Stark, Raymond I.; Hofer, Myron A.; Garland, Marianne; Glickstein, Sara B.; Brunelli, Susan A.; Ludwig, Robert J.; Myers, Michael M.
<x xml:space="preserve">Abstract</x> Background Preterm infants are at high risk for adverse neurodevelopmental and behavioral outcomes. Family Nurture Intervention (FNI) in the Neonatal Intensive Care Unit (NICU) is designed to counteract adverse effects of separation of mothers and their preterm infants. Here, we evaluate effects of FNI on neurobehavioral outcomes. Methods Data were collected at 18 months corrected age from preterm infants. Infants were assigned at birth to FNI or standard care (SC). Bayley Scales of Infant Development III (Bayley‐III) were assessed for 76 infants (SC, n = 31; FNI, n = 45); the Child Behavior Checklist (CBCL) for 57 infants (SC, n = 31; FNI, n = 26); and the Modified Checklist for Autism in Toddlers (M‐CHAT) was obtained for 59 infants (SC, n = 33; FNI, n = 26). Results Family Nurture Intervention significantly improved Bayley‐III cognitive (p = .039) and language (p = .008) scores for infants whose scores were greater than 85. FNI infants had fewer attention problems on the CBCL (p < .02). FNI improved total M‐CHAT scores (p < .02). Seventy‐six percent of SC infants failed at least one of the M‐CHAT items, compared to 27% of FNI infants (p < .001). In addition, 36% of SC infants versus 0% of FNI infants failed at least one social‐relatedness M‐CHAT item (p < .001). Conclusions Family Nurture Intervention is the first NICU intervention to show significant improvements in preterm infants across multiple domains of neurodevelopment, social‐relatedness, and attention problems. These gains suggest that an intervention that facilitates emotional interactions between mothers and infants in the NICU may be key to altering developmental trajectories of preterm infants.